Two new Pseudorchomene species from the Southern Ocean, with phylogenetic remarks on the genus and related species (Crustacea: Amphipoda: Lysianassoidea: Lysianassidae: Tryphosinae) - D’acoz, Cedric D’udekem; Havermans, Charlotte (Zootaxa, 2012)
Two new lysianassoid amphipods of the genus Pseudorchomene Schellenberg, 1926 from the Southern Ocean are de-scribed: P. debroyeri sp. n. collected in baited traps deployed around the Falkland Islands, Burdwood Bank and Îles Ker-guelen between 55 and 470 m, and P. lophorachis sp. n. collected in baited traps and Agassiz trawls deployed in the Scotiaand Weddell Seas at depths between 847 and 1943 m. P. lophorachis sp. n. is characterized by an strongly elongated firstgnathopod and by the occurrence of low posterodorsal humps on the body segments. P. debroyeri sp. n. is very similar toP. coatsi (Chilton, 1912) but exhibits slight differences of proportions in the articles of gnathopods 1 and 2, more spineson pereopods and more acute spines on the propodus of pereopods 3–7. Molecular data indicate the existence of a well-defined clade comprising P. lophorachis sp. n., P. debroyeri sp. n., P. coatsi (Chilton, 1912), Abyssorchomene plebs (Hur-ley, 1965) and A. rossi (Walker, 1903). On the other hand, A. plebs and A. rossi do not form a clade with A. chevreuxi(Stebbing, 1906), which is the type species of the genus Abyssorchomene De Broyer, 1984. The definition of Pseudor-chomene is amended, so that it now includes P. coatsi, P. debroyeri, P. lophorachis, P. plebs and P. rossi. The triangularcoxa 1 in these 5 species is unique for ‘orchomenid’ lysianassoids, thus considered as a putative synapomorphy. P. coatsi(Antarctic species) is morphologically extremely similar to P. debroyeri (sub-Antarctic species) but it is genetically closer to the morphologically distinct P. lophorachis (Antarctic species). Hypotheses for these recent speciations and the mor-phological evolution within Pseudorchomene are discussed. The type species and the nomenclatural history of the genus Tryphosa Boeck, 1871, which is the type genus of the subfamily Tryphosinae, are discussed.